2012
DOI: 10.1002/ejsp.1914
|View full text |Cite
|
Sign up to set email alerts
|

Attachment, perceptions of care and caregiving to romantic partners and friends

Abstract: Across two studies, we examined the extent to which adults' caregiving responses reflect the quality of care received from their attachment figures. Study 1 showed that romantic caregiving reflected the quality of perceived parental and partner care. Moreover, perceived partner care mediated the link between parental care and romantic caregiving, suggesting that one's parental care affects the type of care one seeks or receives from partners, which in turn affects one's romantic caregiving. This describes a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 41 publications
(115 reference statements)
3
13
0
Order By: Relevance
“…Furthermore, the CQ specific factors tended to correlate with constructs from attachment theory in the expected directions, providing additional data on the validity of this instrument. As anticipated, attachment anxiety was more strongly associated with controlling and compulsive caregiving, while attachment avoidance was more strongly connected with low proximity and sensitivity, findings that are in line with previous evidence [ 15 , 16 , 18 , 22 ]. These results can represent the tendency to become overly involved in the case of people with higher attachment anxiety, even though they experience concern for their partner´s welfare [ 7 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Furthermore, the CQ specific factors tended to correlate with constructs from attachment theory in the expected directions, providing additional data on the validity of this instrument. As anticipated, attachment anxiety was more strongly associated with controlling and compulsive caregiving, while attachment avoidance was more strongly connected with low proximity and sensitivity, findings that are in line with previous evidence [ 15 , 16 , 18 , 22 ]. These results can represent the tendency to become overly involved in the case of people with higher attachment anxiety, even though they experience concern for their partner´s welfare [ 7 ].…”
Section: Discussionsupporting
confidence: 91%
“…Among those with high levels of attachment anxiety, hyperactivation of the care system is observed, which leads them to be intrusive and hyper-vigilant, assuming a leading role in solving problems, or displaying exaggerated reactions that control or limit the partner’s actions. Accordingly, it has been reported that people with greater attachment anxiety, although seeking intimacy with others, tend to provide ineffective care, given that the motivation for caregiving would respond more to self-centered needs: either to reduce the distress generated by the partner’s vulnerability, or the need to be recognized and validated [ 11 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although secure individuals are able to accurately identify distress and provide the support needed, highly anxious and avoidant individuals have greater difficulty with caregiving [ 12 ]. Specifically, highly anxious individuals attempt to prove their worth when providing care [ 14 ], resulting in more aversive and less effective caregiving because their responses are more self-focused [ 15 , 16 , 17 , 18 ]. Highly avoidant individuals are generally poor caregivers [ 18 , 19 ] because they are lower in prosocial motivation and lower in emotional intimacy with their partner [ 12 ], which is necessary for more targeted and appropriate support-giving.…”
Section: Introductionmentioning
confidence: 99%